Completion and determinants of a continuum of care in maternal health services in Benishangul Gumuz region: A prospective follow-up study - Zelka, Muluwas Amentie; Yalew, Alemayehu Worku; Debelew, Gurmesa Tura (Frontiers in Public Health, 2022)
Introduction The provision of a continuum of care to women throughout pregnancy, labor, and after delivery has become a fundamental strategy for improving maternal and neonatal health. A better understanding of where the gaps are in seeking care along the pathway and what factors contribute to the gaps is required for successful program implementation. Hence, this study was targeted to determine the status and determinant factors of the completion rate of a continuum of care in maternal health services. Methods A prospective follow-up study was conducted among 2,198 sampled pregnant women and followed for 11 months in Benishangul-Gumuz region. A multistage clustered sampling technique was employed to select the study participants. Data were collected via face-to-face interviews using a pretested, semi-structured questionnaire, and logbook registry. Collected data were edited, cleaned, and analyzed using STATA software. The multilevel regression model was used to examine the effects of individual- and community-level factors and expressed as AOR with 95% CI. Results The completion rate of a continuum of care via visit-based, content-based, and space dimensions was 33.1, 20, and 37.2%, respectively. The enabling factors were having information on maternal health services (AOR = 2.25; 95% CI: 1.11–4.55), iron and folic acid supplementation (AOR = 2.58; 95% CI: 1.37–4.86), tetanus toxoid vaccination during pregnancy (AOR = 2.21; 95% CI: 1.39–3.52), having pregnant-related problems (AOR = 2.1; 95% CI: 1.15–3.71), dry and stimulate newborn (AOR = 2.61; 95% CI: 1.42–4.77), appropriate cord care (AOR = 2.01; 95% CI: 1.07–3.79), and immunizing newborn (AOR = 6.9; 95% CI: 3.79–12.59), whereas risk factors were ever having a stillbirth (AOR = 0.52; 95% CI: 0.32–0.85) and delay of 1st ANC initiation at 4–6 months of pregnancy (AOR = 0.45; 95% CI: 0.3–0.68). Conclusion The completion rates via visit-based, content-based, and space dimensions were low. Different determinant factors which have a programmatically important implication were identified. Thus, interventions should focus on increasing women's awareness and improving the availability and accessibility of the whole packages of maternal health services to facilitate the completion rate.